Immunopathological response of the body in patients with chemosensitive and drug-resistant pulmonary tuberculosis - Sakhelashvili , Manana; Platonova, Iryna; Lapovets, Lyubov; Zubchenko, Svitlana (ScienceRise: Medical Science, 2023)
Immunological methods are important for diagnosing tuberculosis, evaluating the process activity, and forecasting the course of the disease and recovery. Materials and methods. 47 patients with first diagnosed destructive sputum smear-positive pulmonary tuberculosis underwent a complex immunoassay. The patients were divided into two groups based on the sensitivity/resistance of mycobacterium tuberculosis to antimycobacterial agents. The first group consisted of 22 patients with first-diagnosed chemosensitive tuberculosis with preserved sensitivity to antimycobacterial agents. The second group consisted of 25 patients with multi-drug resistant tuberculosis pulmonary tuberculosis (MDR-TBP). The research was conducted during the 2018-2021 years. Results Specific cell response disorders in patients with pulmonary tuberculosis are associated with the multi-structural T-cell protection misbalance caused by the quantitative changes of its components, the increase/decrease in the quantity of certain lymphocyte pools specifying the immune response vector. In cases of tuberculosis, phagocytosis plays an important role. Phagocytosis might release cells from the tuberculosis pathogen. To achieve this, the activation of cells should reach a certain level. However, the initial protective nature of cell activation might become aggressive. The T-cell immunity disorders were more evident in patients with MDR-TBP versus donors and patients with chemosensitive tuberculosis. The apparent decrease in СD3+СD56+, СD3+СD4+ pools and the increase in СD3+СD8+ were revealed in cases of MDR-TBP tuberculosis versus chemosensitive tuberculosis. The difference in СD3+СD4+, СD3+СD8+, СD3+СD4+/СD3+СD8+, CD3+СD8+HLA-DR+, СD16/56+8+ between the study and observational groups was statistically confirmed. The evident specific cell immunity disorders in patients with MDR-TBP aggravate the clinical course of the disease, causing destructive changes and acute and extensive processes. Conclusions Changes in different components of the immune system might occur during pulmonary tuberculosis (in T- and B-cells, phagocytic cells), specific and enzymatic processes are activated, and autoimmunization is evident. The intensity of the changes varies at different stages of the disease. Most immune disorders caused by the specific inflammation process require immune correction.